NEUTROPHIL LYMPHOCYTE RATIO (NLR) AS DIAGNOSTIC MARKER IN CHILDREN WITH DENGUE FEVER (The Research of Medical Science Review, 2025)
Objective: To compare the sensitivity and specificity of the neutrophil lymphocyte ratio (NLR) in diagnosing dengue fever pediatric patients at a tertiary care center Study Design: Analytical Cross sectional study Place and Duration of Study: Department of Pediatrics, Fauji Foundation Hospital, Rawalpindi from Jun 2024-Dec 2024 Methodology: 140 children fulfilling selection criteria were enrolled from pediatric emergency. Blood complete picture and dengue IgM serology was sent in all patients. Patients were labeled as dengue positive on NLR if calculated NLR was <1.63 and if IgM levels were >2.85. Primary variables observed were sensitivity and specificity of the neutrophil lymphocyte ratio in diagnosing dengue fever. Results: According to defined cut-off values as per the study design, patients with NLR results suggestive of dengue fever were 98 (70.0%) while patients with dengue IgM results suggestive of dengue were 61 (43.6%) patients. Sensitivity and specificity of NLR when compared with gold standard dengue IgM results showed a sensitivity of 57.1%, with a specificity of 88.1%, with a false positive rate of 11.9% and a false negative rate of 42.9% Conclusion: The study concludes that NLR has satisfactory sensitivity but good specificity as a diagnostic marker for dengue fever and can be used where IgM serology is not available.